2019
DOI: 10.1002/mpr.1760
|View full text |Cite
|
Sign up to set email alerts
|

Proactive multipurpose health risk screening in health care settings: Methods, design, and reach

Abstract: Objectives Real world implementation of proactive screening and brief intervention in health care is threatened by high cost. Using e‐health interventions and screening for multiple health risk factors may provide more efficiency. We describe methodological details of a proactive multipurpose health risk screening in health care settings and report on participation rates, participants' characteristics, and participation factors. Methods Patients between 18 and 64 years from ambulatory practices and hospitals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Energy-balance related HRF profiles were particularly common in the total sample. With a proportion of 22%, overweight plus inactivity was the most common HRF profile as also found in a general population and in a general hospital study in Germany [11,44]. Similar to a previous general hospital study that investigated the HRFs smoking and alcohol only [57], our findings showed that about half of the hospital patients reported at least one of the two substance-use related HRFs.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Energy-balance related HRF profiles were particularly common in the total sample. With a proportion of 22%, overweight plus inactivity was the most common HRF profile as also found in a general population and in a general hospital study in Germany [11,44]. Similar to a previous general hospital study that investigated the HRFs smoking and alcohol only [57], our findings showed that about half of the hospital patients reported at least one of the two substance-use related HRFs.…”
Section: Discussionsupporting
confidence: 88%
“…The second limitation concerns the generalizability of our findings to patients from other departments, or to other general hospitals in Germany or beyond. A multisite study in Germany, however, revealed similar proportions of the single HRFs [44]. The third limitation concerns that some significant differences in proportions between subgroups may have been missed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For this purpose, a consecutive sample of medical care patients is used. Medical care provides a valuable setting for studying and managing alcohol use and depressive symptoms, given the frequent presentation of both conditions due to accompanying physical health problems [3,12,13].…”
Section: Introductionmentioning
confidence: 99%